Pengaruh Penerapan Model Pembelajaran Project Based Learning Terhadap Hasil Belajar Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti - Mohammad Kurjum; Mughnillabib Muhammad; Ali Hasan Siswanto (Indonesian Journal of Humanities and Social Sciences, 2023)
This article is written based on three problem formulations, namely (1) how is the Application of the Project Based Learning Model to the Learning Outcomes of Islamic Religious Education Subjects and Budi Pekerti at SMK BP Subulul Huda Kembangsawit?, (2) What are the advantages and disadvantages of the Project Based Learning Model to the Learning Outcomes of Islamic Religious Education Subjects and Budi Pekerti at SMK BP Subulul Huda Kembangsawit?, and (3) Is there an Effect of the application of the Project Based Learning Model on the Learning Outcomes of Islamic Religious Education Subjects and Budi Pekerti at SMK BP Subulul Huda Kembangsawit?. This research results that first; the Project Based Learning method is a fitting and suitable method applied to Islamic Religious Education and Budi Pekerti material. Second, there are several advantages and disadvantages in the application of PJB method. Third, the application of the PJBL method is very influential on the achievement (learning outcomes) of SMK BP Subulul Huda Kembangsawit students, this is evidenced by the results of the above calculations which are very significant.